What are the determinants of vegetable intake among adolescents from socioeconomically disadvantaged urban areas? A systematic review of qualitative studies - Silvia Bel-Serrat; Antje von der Schulenburg; Maria Marques-Previ; Amy Mullee; Celine M Murrin (BMC, 2022)
Abstract Background Evidence available on the determinants of vegetable intake in young populations is inconsistent. Vegetable intake is particularly low in adolescents from less-affluent backgrounds, yet no systematic review of qualitative studies investigating determinants for vegetable intake specifically has been conducted to date in this group. This systematic review aimed to identify determinants of vegetable intake in adolescents from socioeconomically disadvantaged urban areas located in very high-income countries reported in qualitative studies. Methods Five electronic databases (PubMed, Web of Science, CINAHL, PsycINFO and ERIC) were searched until August 2022. The search strategy used combinations of synonyms for vegetable intake, adolescents, and qualitative methodologies. Main inclusion criteria were studies exploring views and experiences of motivators and barriers to vegetable intake in a sample of adolescents aged 12-18 years from socioeconomically disadvantaged urban areas in very high income countries. Study quality assessment was conducted using criteria established in a previous review. Results Sixteen studies were included out of the 984 screened citations and 63 full texts. The synthesis of findings identified the following determinants of vegetable intake: sensory attributes of vegetables; psychosocial factors (nutrition knowledge, preferences/liking, self-efficacy, motivation); lifestyle factors (cost/price, time, convenience); fast food properties (taste, cost, satiety); home environment and parental influence; friends' influence; school food environment, nutrition education and teachers' support; and availability and accessibility of vegetables in the community and community nutrition practices. Studies attained between 18 and 49 out of 61 quality points, with eleven of 16 studies reaching ≥ 40 points. One main reason for lower scores was lack of data validation. Conclusion Multiple determinants of vegetable intake were identified complementing those investigated in quantitative studies. Future large scale quantitative studies should attempt to examine the relative importance of these determinants in order to guide the development of successful interventions in adolescents from socioeconomically disadvantaged backgrounds.